Revitalisasi Taman Pendidikan Al-Qur’an Al Mahri Desa Pedagangan Kec. Dukuhwaru Kab. Tegal - Sarja; Masturoh, Siti Apriliana; Rifa’i, Zainas Zidan Rifa’i; Fitriyani, Zulfa Rizkia; Sya’bani, Eka Rizqi Nur; Isnawansyah, Ervan; Alfia, Esya; Izzah, Fitriyatun; Faida, Naila; Fitri, Nurhikmah Idul; Salsabila, Nelu (Profetik: Jurnal Pengabdian Masyarakat, 2024)
TPQ Al Mahri is a religious education institution which has an important role in shaping the character and spiritual intelligence of children in Pedagangan Village, Dukuhwaru District, Tegal Regency. However, in recent years, TPQ Al Mahri has faced challengers in terms of infrastructure, curriculum, and community involvement in managing TPQ, which has been in a vacuum for three years. This study aims to explore the condition of TPQ Al Mahri which has been experiencing problems in the teaching and curriculum sectors. The research method used is a case study with a qualitative approach. Data was collected through in-depth interviews with various parties related to TPQ Al Mahri, participant observation, and document analysis. The results of the research show that with the presence of IBN Tegal KKN students, TPQ Al Mahri is revitalized so that teaching and learning activities run well and all of this cannot be separated from improving infrastructure, increasing the quality of curriculum, as well as strengthening the involvement of the trading village community through participatory programs. With the revitalization of IBN Tegal KKN students, it is hoped that TPQ Al Mahri can generation with noble character and broad knowledge in the Islamic religion.